Evaluation of cauliflower genotypes by different growing method - Gulyás, G.; Tóth, A. R.; Takácsné Hájos, M. (International Journal of Horticultural Science, 2019)
Cauliflower is currently cultivated on 350-400 thousand hectares in the world and around 1500 ha in Hungary. Its cultivation requires considerable expertise as it is sensitive to environmental factors and adequate nutrient supply. The aim of our experiment was to compare three genotypes (Abeni, SV5777 AC and Telergy F1) by different growing method – under plastic tunnel and on open field. On open field the planting was on 19th of March, 2018, the row and plant distances were 45 and 35 cm. Under plastic tunnel the transplants were set out on the same day with the same genotypes as on open field, with 55x45 cm arrangement. The results have proved that cauliflower curds from plastic tunnel was two times bigger than on open field. The more protected environment had a positive effect not only on the mass of the curd, but also on the biomass production. Among the examined genotypes Abeni showed the highest yield (about 1 kg/plant) under plastic tunnel. The shape of the head is important for the market. According to our data, we measured the width and height of the curd. Open field conditions induced wider curd with longer stem and caused lower product quality and weaker correlation between the parameters than plastic tunnel.